Interaction of Avelox with Bovine Serum Albumin and Effect of the Coexistent Drugs on the Reaction - Baosheng Liu; Chao Yang; Xiaona Yan; Jing Wang; Yunkai Lv (International Journal of Analytical Chemistry)
The interaction between Avelox and bovine serum albumin (BSA) was investigated at different temperatures by fluorescence spectroscopy. Results showed that Avelox could quench the intrinsic fluorescence of BSA strongly, and the quenching mechanism was a static quenching process with Förester spectroscopy energy transfer. The electrostatic force played an important role on the conjugation reaction between BSA and Avelox. The order of magnitude of binding constants (Ka) was 104, and the number of binding site (n) in the binary system was approximately equal to 1. The binding distance (r) was less than 3 nm and the primary binding site for Avelox was located in subdomain IIA of BSA. Synchronous fluorescence spectra clearly revealed that the microenvironment of amino acid residues and the conformation of BSA were changed during the binding reaction. In addition, the effect of some antibiotics on the binding constant of Avelox with BSA was also studied.